Low-level auricular vagus nerve stimulation lowers blood pressure and heart rate in paroxysmal atrial fibrillation patients: a self-controlled study - Yu Jiang; Yu Jiang; Di Su; Jingwen Xiao; Jingwen Xiao; Wenbo Cheng; Yuemei Hou; Yan Zhang; Yan Zhang (Frontiers in Neuroscience)
ObjectiveTo investigate the effects of low-level auricular vagus nerve stimulation (LL-aVNS) on blood pressure and heart rate in patients with paroxysmal atrial fibrillation.MethodsA total of 22 patients with paroxysmal atrial fibrillation diagnosed in Fuzhou First General Hospital Affiliated with Fujian Medical University from September 2021 to December 2022 were selected and given LL-aVNS treatment based on the original unchanged drug treatment for 4 weeks. The systolic blood pressure (SBP), diastolic blood pressure (DBP), heart rate maximum (HRmax), heart rate minimum (HRmin), left ventricular ejection fraction (LVEF), left atrial diameter (LAD), Atrial Fibrillation Severity Scale (AFSS) symptom subscale, and Memorial Symptom Assessment Scale-Heart Failure (MSAS-HF) before and after the treatment were observed and compared. In addition, adverse effects of the LL-aVNS procedure and 6-month follow-up were recorded.ResultsSBP, DBP, and HRmin were lower after the treatment than before the treatment (p < 0.05); AFSS symptom subscale scores and MSAS-HF scores after the treatment were lower before the treatment (p < 0.05); itching of the skin was observed in one case during the course of LL-aVNS; and two patients were hospitalized for acute exacerbation of chronic heart failure between 4 months and 6 months after the treatment.ConclusionLL-aVNS in patients with paroxysmal atrial fibrillation can assist in controlling blood pressure and heart rate, effectively relieving symptoms, and the treatment process is safe and feasible.